Dynamic fracture toughness of magnesium alloy under impact loading conditions - Mohd Ahadlin, Mohd Daud; Nurulhilmi Zaedah, Nasir; Ahmad, Rivai; Mohd Zulkefli, Selamat (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.